An Experimental and Theoretical Investigation of the Ring‐Opening Polymerization of L, L‐Lactide. Issue 12 (3rd September 2014) - Pladis, Prokopios; Karidi, Konstantina; Mantourlias, Theofanis; Kiparissides, Costas
Abstract A comprehensive mathematical model was developed based on a detailed kinetic mechanism to predict the dynamic evolution of monomer conversion and molecular weight averages. The predictive capabilities of the mathematical model are demonstrated by a direct comparison of model predictions with literature and new experimental data on monomer conversion as well as number and weight average molecular‐weight of PLLA. The effects of monomer to initiator molar ratio and polymerization temperature on the polymerization rate and average molecular weight properties of polylactide were experimentally determined and compared with model predictions. For this reason, high molecular weight polylactides were synthesized in melt via the ring‐opening polymerization of L, L‐lactide, in the presence of stannous octoate.<inline-graphic xlink:href="ark:/27927/pgh2qw3jdkc" content-type="mren201400032-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />